Iowa Birdline update, May 19, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for May 19, 1992. The highlights for the update include sightings of a singing Prairie Warbler and a singing Worm-eating Warbler both at the Croton Unit of Shimek State Forest and several Yellow-Crowned Night Herons at Sullivan Slough. Also included are handwritten notes with sightings of Piping Plovers, White-rumped Sandpipers and a Black-billed Cuckoo. Epson - sheet feed/flatbed